Transporter Selection Based on Supply Chain Management (SCM) Criteria Using Analytical Hierarchy Process (AHP) - Chairuddin, Irwan; Hanifah, Hanifah (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2014)
A company manager should be able to decide which transporter could be used and make sure the product arrives in time to the consumerâs address. It is expected that the manager could choose the transporter based on desired criteria using the method of AHP.